2017
DOI: 10.1002/jcb.25961
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of Mesenchymal Stromal Cells With Low and High Doses of Alpha Particles Induces Senescence and/or Apoptosis

Abstract: The use of high-linear energy transfer charged particles is gaining attention as a medical tool because of the emission of radiations with an efficient cell-killing ability. Considerable interest has developed in the use of targeted alpha-particle therapy for the treatment of micrometastases. Moreover, the use of helium beams is gaining momentum, especially for treating pediatric tumors. We analyzed the effects of alpha particles on bone marrow mesenchymal stromal cells (MSCs), which have a subpopulation of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…However, in the present study, the effect was not significant. It might be owing to the effect becoming impaired when secretomes were collected from senescent cells previously in contact with cancer cells as reported before (Özcan et al , 2015; Alessio et al , 2017).…”
Section: Discussionmentioning
confidence: 73%
“…However, in the present study, the effect was not significant. It might be owing to the effect becoming impaired when secretomes were collected from senescent cells previously in contact with cancer cells as reported before (Özcan et al , 2015; Alessio et al , 2017).…”
Section: Discussionmentioning
confidence: 73%
“…A significant difference in apoptosis but not senescence was observed between the P6 and P10 BMSCs after irradiation. However, BMSCs were shown to be prone to senescence rather than apoptosis after exposure to a low radiation dose in previous studies [35, 36]. Generally, BMSCs at late passages should be more resistant to apoptosis since they should have a higher percentage of senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…concerning the direct damage of irradiation to biological function in osteocytes, irradiation can markedly inhibit the viability and proliferation of osteocytes, which ultimately leads to a decreased number of osteocytes in a dose-dependent manner. Although a high dose of radiation tends to induce more apoptosis and necrosis, previous research had demonstrated that the initial apoptotic cells tend to die rapidly, and the majority of surviving cells maintain senescence (46)(47)(48). Given these evidences, at 5 days after radiation a small number of apoptosis or necrosis osteocytes were inevitably mixed into exiting populations, while the majority of surviving cells maintain senescence.…”
Section: Discussionmentioning
confidence: 99%